Analisis Internal Perusahaan (Strength & Weakness), Menggunakan konsep ‘Resource-Based View of the Firm’ dengan Kerangka VRIO - Son Wandrial (Bina Nusantara University, 2011)
Problems in the company's internal environmental analysis is to determine the strengths and weaknesses (internal resources), we did not have reasonable grounds to determine whether the company's internal resources as a strength or weakness. Before we can determine whether a resource can be categorized as strengths or weaknesses, we must have a certain criteria so that appropriate resources are said to be a strength or weakness